Image Building Strategy on the Example of Selected Polish Regions - Stanowicka, Agnieszka (Olsztyn Economic Journal, 2014)
The objective of this study was to identify and evaluate image building strategies in selected Polish regions. A mail questionnaire survey was carried out in 2013 in the regions of Pomorze (Pomerania), Pomorze Zachodnie (West Pomerania), Małopolska (Lesser Poland), Podkarpacie (Subcarpathia), Warmia and Mazury (Warmia and Masuria), and Podlasie. The importance of image building strategies is widely recognized by the local authorities, but most strategies are implemented on a short-term or medium-term basis. Image building strategies are often regarded as auxiliary measures that contribute to the achievement of strategic development goals. In the analyzed regions, image building is often reduced to strictly promotional measures. The relevant strategies focus on too many landmarks of regional identity, which detracts from their effectiveness. An absence of regular market surveys and evaluations also contributes to the weakness of regional image building strategies.